Dominican Republic : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that after three years of robust expansion, the economy of the Dominican Republic moderated to close to its potential level. Economic activity is estimated to have expanded by 4.6 percent in 2017, following above-potential growth of 7.1 percent on average during 2014-16. The growth moderation was concentrated in the first three quarters of 2017. The economic outlook remains positive. The monetary easing in mid-2017 is expected to support a continued recovery in economic activity in 2018. Lower lending rates and stronger credit growth following the easing, combined with higher real wages and employment, are expected to continue to support domestic demand.